Progress of bone marrow mesenchymal stem cell transplantation on neural plasticity in brain - Li, Wenjing; Liu, Xiaohua; Li, Jingjing (Frontiers in Cell and Developmental Biology, 2025)
Stem cells are cells with strong proliferation and differentiation abilities. Among all stem cells, bone marrow mesenchymal stem cells (BMSCs) have been extensively studied. BMSCs have the ability to self-renew and differentiate into nerve cells, and participate in cell migration and survival. These cells can also secrete neurotrophic factors through paracrine pathways to affect neural plasticity. Transplantation of BMSCs can affect neural plasticity and is the main treatment method for stroke or other traumatic brain diseases. This article elaborates on the role of BMSC transplantation in neural plasticity, neurotrophic factors, and synaptic changes, and comprehensively analyzes its potential molecular mechanisms to provide a theoretical basis for clinical treatment of brain diseases.